Answer :


Given :


To prove :


Formula used : =


=



= 1


If u and v are functions of x,then = u + v


The CHAIN RULE states that the derivative of f(g(x)) is f’(g(x)).g’(x)


.


y =


squaring on both sides


= x + y


Differentiating with respect to x


2y = 1 +


(2y – 1) = 1


=


=


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses